Ion source for Bendix Mass Spectrometer - Bendix Corporation (1957)
Close-up view of a portion of the ion source for a Bendix Corporation Mass Spectrometer. One of four component parts of a mass spectrometer, the ion source produces a beam of particles characteristic of the sample material for qualitative and quantitative analysis. Per notations accompanying the photograph, this apparatus was designed to hold a Model 102 Magnetic Electron Multiplier.
Keywords: Scientific apparatus and instruments; Spectrometer industry; Mass spectrometry; Time-of-flight mass spectrometry; Bendix Corporation; Ion sources; Mass spectrometers